Ion beam analysis of rubies and their simulants - Juncomma U. (Elsevier, 2014)
Ion beam analysis (IBA) is a set of well known powerful analytical techniques which use energetic particle beam as a probe. Among them, two techniques are suitable for gemological analysis, i.e., Particle Induced X-rays Emission (PIXE) and Ionoluminescence (IL). We combine these two techniques for the investigations of rubies and their simulants. The main objective is to find a reference fingerprint of these gemstones. The data are collected from several natural rubies, synthetic rubies, red spinels, almandine garnets and rubellite which very much resemble and are difficult to distinguish with the gemologist loupe. From our measurements, due to their different crystal structures and compositions, can be clearly distinguished by the IL and PIXE techniques. The results show that the PIXE spectra consist of a few dominant lines of the host matrix elements of each gemstone and some weaker lines due to trace elements of transition metals. PIXE can easily differentiate rubies from other stones by evaluating their chemical compositions. It is noticed that synthetic rubies generally contain fewer impurities, lower iron and higher chromium than the natural ones. Moreover, the IL spectrum of ruby is unique and different from those of others stones. The typical spectrum of ruby is centered at 694 nm, with small sidebands that can be ascribed to a Cr3+ emission spectrum which is dominated by an R-line at the extreme red end of the visible part of the electromagnetic spectrum. Although the spectrum of synthetic ruby is centered at the same wavelength, the peak is stronger due to higher concentration of Cr and lower concentration of Fe than for natural rubies. For spinel, the IL spectrum shows strong deformation where the R-line is split due to the presence of MgO. For rubellite, the peak center is shifted to 692 nm which might be caused by the replacement of Mn3+ at the Al 3+ site of the host structure. It is noticed that almandine garnet is not luminescent due to the idiochromatic nature of the stone. © 2014 Elsevier B.V. All rights reserved.